Numerical Modeling of Reactive Transport and Self-Sealing Processes in the Fault-Controlled Geothermal System of the Guide Basin, China - Zhaoyun Hou; Tianfu Xu; Guanhong Feng; Bo Feng; Yilong Yuan; Zhenjiao Jiang (Geofluids)
Strong chemical reactions in the geothermal systems may cause sealing of fractures, which reduces the permeability in the reservoir and subsequently affects the heat production. However, it is difficult to reveal the sealing range in a deeply buried reservoir based on a limited number of downhole logs. This study recreated the sealing processes of the fault-controlled geothermal system in the Guide Basin, China, by reactive transport modeling. The modeling domain was discretized based on multiple interacting continua (MINC) approach, to address the nonequilibrium heat transport processes between the matrix and conduit in the fractured fault damage zone. Once the model was validated by observations of major ions in spring water and downhole temperature logs in the discharge area, it was used to determine the coupled processes of fluid, heat, and chemical transport in the reservoir and the resultant sealing ranges. It was found that the dissolution of albite and K-feldspar leads to the precipitation of smectite-Ca and illite in the middle and bottom of the fault under the condition of high concentration of Ca2+ and Mg2+ in the recharge water. Calcite veins were formed in discharge zone, because the horizontal fast flow in shallow subsurface zone supplied abundant Ca2+ and HCO3-. As a consequence, the permeability in the discharge zone reduced by 15% when compared to the original permeability of 100 mD. Moreover, another three self-sealing areas were formed near the recharge zone, the deep upgradient zone, and the downgradient area where the fast upward fluid flow occurred. Self-sealing subsequently prevented the deep circulation of the flow and heat absorption, which tends to make the fault-controlled geothermal system inactive.